RCM gateway to world class maintenance - Smith, Anthony M.; Hinchcliffe, Glenn R. (Amsterdam ; Boston : Elsevier Butterworth-Heinemann, 2004)
Reliability-Centered Maintenance provides valuable insights into current preventive maintenance practices and issues, while explaining how a transition from the current "preserve equipment" to "preserve function" mindset is the key ingredient in a maintenance optimization strategy. This book defines the four principal features of RCM and describes the nine essential steps to achieving a successful RCM program. There is an easy to follow example illustrating the Classical RCM systems analysis process using the water treatment system for a swimming pool. As well as the use of software in the system analysis process, making a specific recommendation on a software product to use. Additionally, this new edition possesses an appendix devoted to discussing an economic model that has been used successfully to decide the most cost effective use of maintenance. Top Level managers, engineers, and especially technicians who rely on PM programs in their plant operations can't afford to miss this inclusive guide to Reliability-Centered Maintenance. *Includes detailed instructions for implementing and sustaining an RCM program for extremely cost effective manufacturing *Presents seven real-world cross-industry RCM sucess case studies that have profited from this plan *Provides essential information on how RCM focuses your maintenance organization to become a recognized "center for profit" *Offers over 35 accumulated years of the authors' experiences in Lessons Learned for the proper use of RCM (and pitfalls to avoid).
A World Class Maintenance Program; A Key Maintenance Strategy; The "R" in RCM -- Pertinent Reliability; Preventive Maintenance Definition and Structure; RCM -- A Proven Approach; Classical RCM Methodology -- The Systems Analysis Process; Illustrating Classical RCM -- A Simple Example; Alternate Analysis Methods; Implementation -- Carrying RCM to the Floor; RCM Lessons Learned; The Living RCM Program; Software Support -- RCM Worksaver; Illustrating RCM Use In Industry.
Includes bibliographical references (p. 331-333) and index.
Keywords: Plant maintenance; Reliability (Engineering).; Maintainability (Engineering); Electronic books